Intervensi Konseling Pranikah untuk Meningkatkan Kesiapan Menikah pada Pemuda di Desa Botuboluo Kecamatan Biluhu Kabupaten Gorontalo - Tiara Ratna Sari; Siti Isnain Ibrahim; Cindy Namirah Thalib; Melsin Melsin Dunggio; Irvan Usman; Mohamad Awal Lakadjo (Fakultas Syariah IAIN Laa Roiba Bogor, 2023)
The need to provide information to youth about the impact of marriage at an early age, and to facilitate youth readiness in preparing for marriage, counseling intervention is needed. The research objectives are (a) to describe the profile of marriage readiness in youth, and (b) to provide services in the form of marriage preparation to test the effectiveness of premarital counseling interventions. The research design used in this study is the One-Group Pretest-Posttest Design. The research stage is adapting the counseling intervention stage using the classical guidance service strategy. The population is all youth who are in the vulnerable early adulthood age in Botuboluo Village, Biluhu District, Gorontalo Regency, and the sample is 25 early adults/unmarried youth. Research findings: (a) the profile of youth marriage readiness before premarital counseling intervention is in the traditional category, and after premarital counseling, intervention is in the harmonious category; and (b) the effectiveness of premarital counseling to improve marriage readiness, there is a difference in scores between the results of the pre-test and post-test results of marriage readiness for youth in Botuboluo Village, Biluhu District, Gorontalo Regency who are given the action. The specific description of the article is discussed further in this article.